The virus of the 'others'? Corona and discursive othering in Arab media. (1st April 2021) - Richter, Carola; Al-Shami, Abdulrahman; Khalifa, Sahar; Osman, Soheir; Mundua, Samuel
The spread of fear of the coronavirus and related insecurities around the pandemic have fuelled nationalist and increased exclusionary tendencies in countries all over the world. In North America, for instance, anti-Asian racism increased when former US President Donald Trump dubbed the virus the 'Chinese virus'. A nationalist agenda has been strengthened in many places, including the Middle East and North Africa (MENA) region; and hateful narratives blaming 'others' for the pandemic, legitimizing a retreat to the protection of national borders and policies, are being spread in different media outlets. This article comparatively investigates processes of othering with regard to COVID-19 in four MENA countries ‐ Egypt, Iraq, Oman and Yemen ‐ and asks, who is held responsible for the coronavirus crisis in different countries? How is othering revealed in media coverage related to COVID-19? What (in)sensitive language can be identified? The study looks at mass media coverage at the peak of the global lockdown during the spring of 2020. The media analysis reveals a strong emphasis on mostly national identities as articulated lines of demarcation in all four cases. A homogenizing and demonizing othering was detected in particular in the cases of Yemen and Egypt, but also Iraq, when blame was attributed to political adversaries. The Omani case was characterized by a more subtle othering that focused strongly on the importance of citizenship.